PTPN14 phosphatase and YAP promote TGFβ signalling in rheumatoid synoviocytes. Issue 5 (11th May 2019) - Bottini, Angel; Wu, Dennis J; Ai, Rizi; Le Roux, Michelle; Bartok, Beatrix; Bombardieri, Michele; Doody, Karen M; Zhang, Vida; Sacchetti, Cristiano; Zoccheddu, Martina; Lonic, Ana; Li, Xiaochun; et al.
Abstract : Objective: We aimed to understand the role of the tyrosine phosphatase PTPN14—which in cancer cells modulates the Hippo pathway by retaining YAP in the cytosol—in fibroblast-like synoviocytes (FLS) from patients with rheumatoid arthritis (RA). Methods: Gene/protein expression levels were measured by quantitative PCR and/or Western blotting. Gene knockdown in RA FLS was achieved using antisense oligonucleotides. The interaction between PTPN14 and YAP was assessed by immunoprecipitation. The cellular localisation of YAP and SMAD3 was examined via immunofluorescence. SMAD reporter studies were carried out in HEK293T cells. The RA FLS/cartilage coimplantation and passive K/BxN models were used to examine the role of YAP in arthritis. Results: RA FLS displayed overexpression of PTPN14 when compared with FLS from patients with osteoarthritis (OA). PTPN14 knockdown in RA FLS impaired TGFβ-dependent expression of MMP13 and potentiation of TNF signalling. In RA FLS, PTPN14 formed a complex with YAP. Expression of PTPN14 or nuclear YAP—but not of a non-YAP-interacting PTPN14 mutant—enhanced SMAD reporter activity. YAP promoted TGFβ-dependent SMAD3 nuclear localisation in RA FLS. Differences in epigenetic marks within Hippo pathway genes, including YAP, were found between RA FLS and OA FLS. Inhibition of YAP reduced RA FLS pathogenic behaviour and ameliorated arthritis severity. Conclusion: In RA FLS, PTPN14 and YAP promote nuclear localisation of SMAD3. YAP enhances a range of RA FLS pathogenic behaviours which, together with epigenetic evidence, points to the Hippo pathway as an important regulator of RA FLS behaviour.